H2 formation from Polycyclic Aromatic Hydrocarbon molecules. (July 2015) - Chen, T; Gatchell, M; Stockett, M H; Delaunay, R; Domaracka, A; Micelotta, E R; Tielens, A G G M; Rousseau, P; Adoui, L; Huber, B A; Schmidt, H T; Cederquist, H; et al.
Synopsis: In this work we study statistical fragmentation of Polycyclic Aromatic Hydrocarbon (PAH) molecules following collisions with keV ions. Dissociation and transition state energies for H- and H2 -emissions from PAHs have been calculated and a simple electronic stopping model has been used to calculate collision-induced internal PAH temperatures. We find that H2 may be formed efficiently from pristine PAHs for internal ion temperatures above 2200 K.